Sultiame pharmacokinetic profile in plasma and erythrocytes after single oral doses: A pilot study in healthy volunteers - Kim Dao; Paul Thoueille; Laurent A. Decosterd; Thomas Mercier; Monia Guidi; Carine Bardinet; Sébastien Lebon; Eva Choong; Arnaud Castang; Catherine Guittet; Luc‐André Granier; Thierry Buclin (Wiley, 2020)
Abstract A pilot study was conducted aiming at specifying sultiame's pharmacokinetic profile, completed by in vitro assays evaluating the intraerythrocytic transfer of sultiame and by a pharmacokinetic model assessing its distribution. Single oral doses of sultiame (Ospolot® 50, 100, and 200 mg) were administered in open‐label to four healthy volunteers. Serial plasma, whole blood, and urine samples were collected. A spiking experiment was also performed to characterize sultiame's exchanges between plasma and erythrocytes in vitro. Pharmacokinetic parameters were evaluated using standard noncompartmental calculations and nonlinear mixed‐effect modeling. The plasma maximal concentrations (Cmax) showed striking nonlinear disposition of sultiame, with a 10‐fold increase while doses were doubled. Conversely, whole blood Cmax increased less than dose proportionally while staying much higher than in plasma. Quick uptake of sultiame into erythrocytes observed in vivo was confirmed in vitro, with minimal efflux. A two‐compartment model with first‐order absorption, incorporating a saturable ligand to receptor binding, described the data remarkably well, indicating apparent plasma clearance of 10.0 L/h (BSV: 29%) and distribution volume of 64.8 L; saturable uptake into an intracellular compartment of 3.3 L with a maximum binding capacity of 111 mg accounted for nonlinearities observed in plasma and whole blood concentrations. Pharmacokinetic characteristics of sultiame are reported, including estimates of clearance and volume of distribution that were so far unpublished. The noticeable nonlinearity in sultiame disposition should be taken into account for the design of future studies and the interpretation of therapeutic drug monitoring results.